IMPLEMENTASI CERTAINTY FACTOR DIAGNOSA PENYAKIT JANTUNG BERBASIS ANDROID - Elmi, Elmi Tiodata; Budianto, Alexius Endy; Aziz, Abdul (Jurnal Fakultas Teknologi Informasi, 2025)
The heart is a vital organ that beats non-stop to pump blood throughout the body, but is targeted by dangerous diseases. Heart disease ranks first as a cause of death in Indonesia. Based on the publication of the Indonesian Ministry of Health (Ministry of Health of the Republic of Indonesia, 2023), an estimated 15.5 out of 1,000 deaths in Indonesia are caused by heart disease. An expert system is a system that tries to adopt human knowledge into computers, so that humans can solve problems like an expert. Efforts to treat heart disease in Indonesia are still hampered by various factors, such as lack of public knowledge about the early symptoms of heart disease, delays in medical treatment due to limited medical personnel, unhealthy lifestyles which are the main risk factors, and limited doctor working hours making it difficult for patients to get access to diagnosis and treatment outside of working hours. The application is made using the certainty factor method, which is a method for measuring confidence in a fact or rule in a diagnosis. Its values ​​range from negative (distrust) to positive (full trust), the certainty factor method was chosen because it can diagnose uncertain situations. The implementation of the Certainty Factor (CF) method produces a high level of confidence in the diagnosis of heart disease, with the conformity of symptoms and diagnosis reaching 89% -99%. Starting with manual calculation of CF, then integrated into the application system. Validation is carried out by comparing the results of the application with expert diagnoses to ensure the accuracy of the diagnosis.